The Mediating Role of Dividend Policy in the Influence of Profitability on Firm Value - Hafidz Izzul Haq; Bambang Mahmudi; Abdul Rosyid (Institute of Advanced Knowledge and Science, 2025)
This study aims to empirically test the effect of profitability on firm value through dividend policy as an intervening variable in raw material sector companies listed on the Indonesia Stock Exchange for the period 2013-2023. The study was conducted because there was a business phenomenon in the research topic, inconsistency of empirical data calculation results with theoretical studies, and inconsistency of previous studies that caused a research gap. The research topic is Firm Value which reflects the present value of expected future income. The dividend policy variable is proxied using the Dividend Payout Ratio (DPR). Profitability is proxied by Return on Assets (ROA), and Firm Value using Price to Book Value (PBV). This research is a type of quantitative research with data collection techniques using documentation techniques derived from the company's financial statements. The research population is a raw material industry sector company with a research period of 11 years. The data analysis technique used in the study is Panel Data Regression and Sobel Test using the Eviews version 12 application with the processed data in the form of panel data. The study shows that profitability does not have a significant effect on firm value, but dividend policy has a negative and significant effect on firm value. The dividend policy variable has a positive and significant effect on firm value. Then, dividend policy is able to mediate the influence of profitability on company value.